DECENTRALIZED ISLAMIC FINANCE: HARNESSING BLOCKCHAIN TECHNOLOGY - Supriadi, Iman; Maghfiroh, Rahma Ulfa; Abadi, Rukhul (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to understand how blockchain technology can be used to build a decentralized Islamic financial system. The method used in this research is literature analysis, which is further validated by case studies. The data analysis process was conducted using Systematic Literature Review (SLR) methodology. The main data sources were scientific publications, academic journals, books, and other reputable materials relevant to the research problem. The results of this study show that Blockchain Technology has the potential to reduce the dangers of corruption, money laundering, and illicit activities in the Islamic financial system. Moreover, the use of blockchain technology in decentralized finance ensures equitable access to participation in the financial ecosystem, thereby promoting the inclusion of minority populations. The challenges in implementing blockchain technology within the context of Islamic banking are also highlighted in this study. The contribution and implementation of this research are expected to offer insights into the potential of blockchain technology in constructing a decentralized Islamic financial system, guiding practitioners and academics toward innovative and sustainable solutions in Islamic finance